2016
DOI: 10.1007/s12230-016-9527-3
|View full text |Cite
|
Sign up to set email alerts
|

Growing Potato Profitably for Organic Dry Matter Production in Western Nebraska

Abstract: Growing potato conventionally for dehydration is not economically feasible. The key cost would be seed under organic farming. The objective is to identify seed-piece sizes and spacings producing a profitable return for potato dehydration in western Nebraska. Atlantic potatoes were grown under dryland conditions using organic practices. Rain was 205, 270, and 360 mm in 2013, 2014, and 2015. Seed-pieces were hand-cut into five weights from 42.5 to 85.0 g and planted in five spacings from 15.2 to 45.7 cm. Seeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The significant variation in number of seed tubers/m 2 between years could be attributed to prevailing weather condition that delayed crop maturity in 2019. This is in line with report by Pavlista (2005) who observed that increase in intra-row spacing decreased the yield of seed tubers and increased the proportion and yield of large tubers, while seed tuber number /m 2 and seed tuber yield increased with decrease in intra-row spacing. This is also in agreement with Tesfa et al (2015) report.…”
Section: Effects Of Nitrogen Wood Ash and Intra-row Spacing On Seed T...supporting
confidence: 93%
“…The significant variation in number of seed tubers/m 2 between years could be attributed to prevailing weather condition that delayed crop maturity in 2019. This is in line with report by Pavlista (2005) who observed that increase in intra-row spacing decreased the yield of seed tubers and increased the proportion and yield of large tubers, while seed tuber number /m 2 and seed tuber yield increased with decrease in intra-row spacing. This is also in agreement with Tesfa et al (2015) report.…”
Section: Effects Of Nitrogen Wood Ash and Intra-row Spacing On Seed T...supporting
confidence: 93%
“…As a result, the SY, TY and NUE for potato genotypes were approximately twice lower in 2021 than in 2020 (Table 2). Lower DMY, TY, and SY under water and higher temperature stress conditions were obtained in previous studies (Kasal et al, 2011;Pavlista, Groskopf, 2016;Aliche et al, 2018). A significant relationship between NUE and precipitation and temperature during the vegetation period due to TY formation was revealed by Kasal et al (2011).…”
Section: Discussionmentioning
confidence: 50%